Children In Conflict With The Law In Criminal Acts Of Sexual Violence - Dewi Prawira Putri; Hernawati RAS (Fox Justi : Jurnal Ilmu Hukum, 2024)
Sexual violence is a serious crime that violates human rights. Based on Law no. 12 of 2022 concerning Crimes of Sexual Violence, minors who commit crimes of sexual violence can still be resolved outside of court. Meanwhile, adult perpetrators must go through the process of inquiry, investigation and prosecution until they go to court. Meanwhile, from the research results obtained, cases of sexual violence committed by minors continue to increase every year and the cases are increasingly complex and diverse. Victims of criminal acts of sexual violence experience trauma, physical impacts, and ostracism in society so that nothing can be replaced, including perpetrators of sexual violence who are minors, so Law no. 12 of 2022 concerning the Crime of Sexual Violence, especially article 23, needs to be reviewed immediately considering that nowadays most minors can access the internet easily and supervision is less strict, thus affecting their sexual behavior. This is certainly detrimental to this nation because children are the nation's next generation in the future.